Synthesis of Virus and Virus-induced RNA in Southern Bean Mosaic Virus-infected Soybean Cell Cultures - Wu, F. S.; Murakishi, H. H. (Journal of General Virology, 1979)
SUMMARY The synthesis of 3H-uridine-labelled complete virus, virus RNA and presumed replicative form (RF) were studied during the replication of southern bean mosaic virus (SBMV) in soybean callus cells. The inoculated cells were pre-incubated at 6 °C for 4 days and then moved to 25 °C to improve the synchronization of virus multiplication. The synthesis of complete virus, measured by the incorporation of 3H-uridine into virions and by infectivity assays, rose rapidly during 0 to 34 h after transfer to 25 °C. An RNA with a mol. wt. approximating to that of the postulated RF of SBMV-RNA and exhibiting partial resistance to RNase digestion was synthesized in significant amounts. This occurred after a 16 to 24 h incubation, preceding the major period of virus RNA synthesis which reached maximum during 40 to 48 h. Pulse-chase experiments, within limits, suggested the possible precursor role of the postulated RF in the synthesis of virus RNA. Accumulation of an RNA with electrophoretic properties similar to the presumptive RF of SBMV-RNA, was found in inoculated cells incubated at 6 °C from 84 to 96 h, suggesting a possible blockage of virus replication at the double-stranded RNA stage in these cells.